2018
DOI: 10.1111/ppa.12947
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in the population structure ofDothistroma septosporumat the site of the first recorded outbreak in Poland

Abstract: In this study, evolution of the genetic structure of the oldest known population of Dothistroma septosporum in Poland was analysed. Dothistroma needle blight was first recorded in Poland in 1990 in a 5‐year‐old plantation, meaning the population is relatively young in terms of evolution and genetic development. The preservation of DNA extracts from other studies allowed examination of the genetic variation of the pathogen over the span of a decade with the use of highly sensitive microsatellite markers. A numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 35 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…Individual population studies have shown unexpected levels of diversity in many populations [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. This diversity indicates that sexual reproduction is more common than previously thought, particularly as the sexual stage (previously known as Mycosphaerella pini ) has only rarely been observed, and the asexual stage is ubiquitous.…”
Section: Introductionmentioning
confidence: 99%
“…Individual population studies have shown unexpected levels of diversity in many populations [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. This diversity indicates that sexual reproduction is more common than previously thought, particularly as the sexual stage (previously known as Mycosphaerella pini ) has only rarely been observed, and the asexual stage is ubiquitous.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors suggest that the equal presence of both mating types and the high genetic diversity of European D. septosporum populations increases the likelihood of sexual reproduction of the fungus and genetic recombination (Adamson et al., 2018; Barnes et al., 2008; Boron et al, 2019; Drenkhan et al., 2013; Groenewald et al, 2007; Mullett, Brown, & Barnes, 2015), as well as increases the possibility of the pathogen to co‐evolve with the native pine hosts (Barnes et al., 2011, 2014; Boroń et al, 2016; Drenkhan et al., 2014, 2016; Kowalski & Jankowiak, 1998; McDonald & Linde, 2002; Perry, Brown, Cavers, Cottrell, & Ennos, 2016; Perry, Wachowiak, et al, 2016; Piotrowska et al., 2017). Recent studies in the UK have shown a high variability in the aggressiveness of the pathogen and in the susceptibility of Scots pine populations to D. septosporum , including the different adaptive capacity of trees to survive and co‐exist with the pathogen (Fraser et al., 2015; Perry, Brown, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, the DNB disease has significantly increased in intensity and severity across Europe and worldwide (Adamson, 2018; Boron et al., 2019; Brown & Webber, 2008; Drenkhan et al., 2016; Kranjec‐Orlović et al., 2019; Woods et al., 2016). In eastern and northern parts of Europe, only D. septosporum is found on native host Pinus sylvestris L. (Adamson et al., 2018; Barnes et al., 2008; Drenkhan, Hantula, Vuorinen, Jankovský, & Müller, 2013; Drenkhan et al., 2016; Fraser, Brown, & Woodward, 2015; Millberg, Hopkins, Boberg, Davydenko, & Stenlid, 2016; Müller, Hantula, & Vuorinen, 2009; Mullett et al, 2018; Solheim, 2012; Solheim & Vuorinen, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations